Evaluation of Drug Management at Selection, Planning, and Procurement Stages with Hanlon Method Improvement Strategy at Aulia General Hospital Blitar - Resti, Indah Ana; Sunarni, Titik; Wijayanti, Tri (Oshada, 2026)
Drug management absorbs up to 50% of hospital operational costs, making it a critical component of hospital efficiency. This study evaluates drug management at selection, planning, and procurement stages at Aulia General Hospital Blitar using national standards and determines improvement priorities using the Hanlon method. A descriptive evaluative design was applied using retrospective document review, interviews, and indicator calculations based on Depkes, SNARS, WHO, and Quick et al. standards. Results showed several indicators below standard: conformity with Fornas (42.98%), available funds for procurement (88.52%), planning conformity with actual use (118%), invoice errors (0.90%), and delayed payments (0.16%). Hanlon analysis revealed that the primary priority problem was insufficient available funds for drug procurement, followed by delayed payments, planning mismatch, invoice errors, and non-conformity with Fornas. The root cause lies in managerial and financial allocation issues rather than technical pharmaceutical procedures. The study concludes that establishing a dedicated pharmaceutical budget and strengthening coordination between doctors and pharmacists are essential strategies for improving drug management efficiency.